Embodiment, expertise, and ethics in early modern Europe : entangling the senses - Eberhart, Marlene L.; Baum, Jacob M. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Embodiment, Expertise, and Ethics in Early Modern Europe highlights the agency and intentionality of individuals and groups in the making of sensory knowledge from approximately 1500 to 1700. Focused case studies show how artisans, poets, writers, and theologians responded creatively to their environments, filtering the cultural resources at their disposal through the lenses of their own more immediate experiences and concerns. The result was not a single, unified sensory culture, but rather an entangling of micro-cultural dynamics playing out across an archipelago of contexts that dotted the early modern European world-one that saw profound transitions in ways people used sensory knowledge to claim ethical, intellectual, and practical authority"--
Introduction: Entangled senses-putting knowledge into practice in early modern Europe / Marlene L. Eberhart and Jacob M. Baum -- A web of sensation and the performance of memory : Dosso's Lamenting Apollo / Marlene L. Eberhart -- The poet and the ear : aural figurations in sixteenth-century French poetry / Corinne Noirot -- The artist David Joris (1501-56) : the prophet of the renewed senses / Gary K. Waite -- Abraham Scultetus and the god of paste : ritual conflict and sensuous Calvinism in the second German reformation / Jacob M. Baum -- Shylock's senses : entangled phenomenologies of difference on early English stages / Holly Dugan -- Written on the body : selves, communities, and the sense of pain in early modern England, 1600-1700 / Jan Frans van Dijkhuizen -- Blinding lights and sensory others in Margaret Cavendish's Blazing world / Andrew Kettler -- "Rather back to Ceylon than to Swabia" : global sensory experiences of Swabian artisans in the service of the Dutch East India Company (VOC) / Philip Hahn -- Afterword: A roundtable discussion-volume contributors explore several key issues, established and emerging, in sensory history / curated by Jacob M. Baum and Marlene L. Eberhart.
OCLC-licensed vendor bibliographic record.
Keywords: Senses and sensation in literature; European literature -- Renaissance, 1450-1600 -- History and criticism; HISTORY / General